Marketing of sugar‐sweetened children's drinks and parents' misperceptions about benefits for young children - Frances Fleming‐Milici; Lindsay Phaneuf; Jennifer L. Harris (Wiley, 2022)
Abstract Despite expert recommendations, US parents often serve sugar‐sweetened children's drinks, including sweetened fruit‐flavoured drinks and toddler milks, to young children. This qualitative research explored parents' understanding of common marketing tactics used to promote these drinks and whether they mislead parents to believe the drinks are healthy and/or necessary for children. We conducted nine focus groups in Washington, DC and Hartford, CT with parents of children (9-36 months) of diverse race/ethnicity and socioeconomic status (N = 50). Semistructured discussions elicited parents' responses to four concepts designed to correct common misperceptions about toddler milks and sweetened fruit‐flavoured drinks (fruit drinks and flavoured waters) by providing information about drink ingredients and potentially misleading marketing tactics. Participants expressed widespread misperceptions about sweetened fruit‐flavoured drinks and toddler milks, including perceived healthfulness and benefits for children and confusion between sweetened and unsweetened drink categories (sweetened fruit‐flavoured drinks vs. juice, toddler milk vs. infant formula). They confirmed that common marketing strategies contributed to misperceptions, including front‐of‐package claims and marketing messages that imply benefits for children and/or hide problematic ingredients; cross‐branding and product extensions from trusted brands; side‐by‐side shelf placement at retailers; lower price than healthier products; and targeted marketing to children and parents. Some parents expressed anger about deceptive marketing and supported increased regulation and consumer education campaigns. Findings support the need for policies to address potentially misleading marketing of sweetened fruit‐flavoured drinks and toddler milks and revealed opportunities to reduce parents' provision of these drinks through countermarketing campaigns communicated via trusted sources.